Outsourcing : the definitive view, applications and implications - Burkholder, Nicholas C. (Hoboken, N.J. : Wiley, 2006)
THE DEFINITIVE RESOURCE ON OUTSOURCINGOutsourcing is the hottest topic in business, and it will likely stay that way. Managers, workers, executives, and almost anyone else involved in any large business will probably have to deal with it one day, in one way or another.
OUT SOURCING: THE DEFINITIVE VIEW, APPLICATIONS, AND IMPLICATIONS; Contents; Introduction; Chapter 1: What Is Outsourcing?; Chapter 2: Who Is Outsourcing?; Chapter 3: Imperatives; Chapter 4: How Do I Begin Outsourcing?; Chapter 5: Vertical Integration and Outsourcing Considerations in the Health-Care Sector; Chapter 6: From the Experts: Life After Outsourcing--A Sourcing Management Model (Outsourcing Is Really Sourcing); Chapter 7: More from the Experts; Conclusion; Glossary of Outsourcing Terms; Outsourcing Companies and Services; Index.
Includes bibliographical references (pages 242-246) and index.
English.
John Wiley and Sons
Keywords: Contracting out; Impartition; BUSINESS & ECONOMICS -- Outsourcing; Contracting out; Contracting out; Outsourcing